The universality of Arabic and the pedagogies of Arab countries - Shaheen, Rania Ahmed Rashid (Journal of Humanities & Social Sciences, 2021)
The research “The Arab world and its pedagogies” dealt with two tracks, the first track: Arabic between Semitic and the components of global languages, and the second track: pedagogies specific to strengthening the status of the Arabic language, using the descriptive method, and it stemmed from several questions raised by the virtual reader about the reasons for including the Arabic language within International and Semitic languages, and the relationship between the terms (global- international- official), and the most important components of the Arabic language that made it among the international languages. Language and international policies that serve the Arabic language.